pengaruh PENGARUH METODE TALAQQI TERHADAP KEMAMPUAN MEMBACA AL-QUR’AN DENGAN TAJWID PADA REMAJA USIA 10 – 15 TAHUN DI TPQ ANWARUL FALAH KABUPATEN LAMPUNG TIMUR: 1. Metode Talaqqi, 2.Kemampuan Membaca Al-Qur’an, 3.Tajwid, 4.TPQ - Vika Desy Wulansari; Agus Pahrudin; Agus Susanti (IAIN Ambon, 2026)
Abstract: The purpose of this study is to analyze the influence of the talaqqi method on the ability to read the Qur'an with tajweed in adolescents aged 10–15 years at TPQ Anwarul Falah, East Lampung Regency. This study uses a quantitative approach with a pre-experimental design of one group pretest-posttest. The research sample amounted to 15 adolescents who were selected by purposive sampling. Data collection was carried out through a test of the ability to read the Qur'an with tajweed before and after the application of the talaqqi method. Data were analyzed using validity, reliability, Shapiro-Wilk normality test, Paired Sample t-test, and effect size Cohen's d. The results showed that all instruments were valid and reliable with a pretest Cronbach's Alpha value of 0.934 and a posttest of 0.911. The results of the normality test showed normal distribution data (p > 0.05). The hypothesis test produced a significance value of 0.000 (p < 0.05), which shows a significant influence of the talaqqi method on the ability to read the Qur'an with tajweed. In addition, the effect size value of 2.14 is in the very large category. Thus, the talaqqi method has proven to be effective in improving the ability to read the Qur'an with tajweed in adolescents at TPQ Anwarul Falah, East Lampung Regency. Improving reading ability can be seen in the aspects of fluency, accuracy of tajweed, and reading fluency.